Correlations of the expression of γδ T cells and their co-stimulatory molecules TIGIT, PD-1, ICOS and BTLA with PR and PIBF in the peripheral blood and decidual tissues of women with unexplained recurrent spontaneous abortion. (28th October 2020) - Liang, Q; Tong, L; Xiang, L; Shen, S; Pan, C; Liu, C; Zhang, H
Summary: Semi-allogeneic embryos are not rejected by the maternal immune system due to maternal–fetal immune tolerance. Progesterone (P) receptor (PR)-expressing γδ T cells are present in healthy pregnant women. In the presence of P, these cells secrete an immunomodulatory protein called progesterone-induced blocking factor (PIBF), which can facilitate immune escape and is important in preventing embryonic rejection. This work investigated the correlations of the expression of γδ T cells and their co-stimulatory molecules T cell immunoglobulin and ITIM domain (TIGIT), programmed cell death 1 (PD-1), inducible co-stimulator (ICOS) and B and T lymphocyte attenuator (BTLA) with progesterone receptor (PR) and progesterone-induced blocking factor (PIBF) in peripheral blood and decidual tissue in women with unexplained recurrent spontaneous abortion (URSA) and normal pregnant (NP) women. We confirmed that γδ T cell proportions and PIBF expression in the peripheral blood and decidua of URSA women decreased significantly, while PR expression in decidua decreased. However, TIGIT, PD-1, ICOS and BTLA expression in γδ T cells in peripheral blood did not change, while TIGIT and PD-1 expression in γδ T cells in decidua increased significantly. Under the action of PHA-P (10 µg/ml), co-blocking of TIGIT (15 µg/ml) and PD-1 (10 µg/ml) antibodies further induced γδ T cell proliferation, but PIBF levels in the culture medium supernatant did not change. At 10 −10 M P, γδ T cells proliferated significantly, and PIBF concentrations in the culture medium supernatant increased. γδ T cells co-cultured with P, TIGIT and PD-1 blocking antibodies showed the most significant proliferation, and PIBF concentrations in the culture medium supernatant were the highest. These results confirm that P is necessary for PIBF production. The TIGIT and PD-1 pathways participate in γδ T cell proliferation and activation and PIBF expression and play important roles in maintaining pregnancy. Graphical Abstract: